POLA PENGELUARAN, PERSEPSI, DAN KEPUASAN KELUARGA TERHADAP PERUBAHAN PENGGUNAAN ENERGI DARI MINYAK TANAH KE LPG - Simanjuntak, Megawati; Kusumo, Rani Andriani Budi; Nasarullah, Mohamammad (Jurnal Ilmu Keluarga dan Konsumen, 2009)
The objectives of this research were to analyze the expenses pattern, perception, and satisfaction level of families among fuel conversion. This research was conducted in two villages, namely Cikarawang Village and Situ Gede Village, District of Bogor on October 2008. Total sample were 30 households consisted of fifteen samples in each village that chosen purposively. The average of expenses of families per month for buying fuel, after the fuel conversion program had been conducted tend to decreased from IDR 96.500,00 per month to IDR 58.800,00 per month after the program or saved the family expenses for IDR 37.700,00 per month. Most of respondents stated agreed that conversion program could decreased the family expenses. The gas gave more advantage compared to kerosene, accepted gas as replacement of kerosene, and there was no force in conducting the conversion program. The satisfaction level showed that, respondents felt saver using kerosene and viewed from the cost to buy fuel, few respondents felt heavy for the gas price. Otherwise, the using of LPG was felt more efisien in time, cleaner, and more practice than kerosene.